Antifungal activity, mechanical properties, and accuracy of three-dimensionally printed denture base with microencapsulated phytochemicals on varying post-polymerization time - Ye-Hyeon Jo; Won-Jun Lee; Ji-Hyun Lee; Hyung-In Yoon (BMC, 2022)
Abstract Background Studies on the antifungal activity, flexural strength, Vickers hardness, and intaglio surface trueness of three-dimensionally printed (3DP) denture bases with microencapsulated phytochemicals with respect to changes in post-polymerization time (PPT) are lacking. Methods Specimens of various shapes and dimensions were fabricated with a 3DP denture base resin mixed with 5 wt% phytoncide-filled microcapsules. Each specimen was subjected to different PPT protocols of 5, 10, 20, and 30 min. Specimens without microcapsules with 5-min PPT were used as the negative control group. Cell colonies were counted to evaluate antifungal activity. Three-point bending and Vickers hardness tests were performed to measure the flexural strengths and hardness of the specimens. Fourier-transform infrared spectrometry was used to inspect the degree of conversion (DC). The intaglio surface trueness was measured using root-mean-square estimates calculated by superimposition analysis. A non-parametric Kruskal-Wallis test or one-way analysis of variance was performed (α = 0.05). Results The specimens with microcapsules and 10-min PPT showed the highest antifungal activity among the tested groups. Compared with the positive control group (5-min PPT), the specimens with PPTs of 10 min or longer showed significantly higher mean flexural strength, higher DC, greater hardness, and better trueness (all, P < 0.05). Except for the difference in antifungal activity, no statistically significant differences were detected between the specimens subjected to 10-, 20-, and 30-min PPT. Conclusion The 3DP denture base filled with microencapsulated phytoncide showed different antifungal activity and physical properties on changing PPT. The 3DP denture base containing phytoncide-filled microcapsules at 5 wt% concentration and subjected to 10-min PPT exhibited sufficient antifungal activity as well as mechanical properties and accuracy within clinical acceptance.